2019
DOI: 10.24843/bf.2019.v20.i02.p05
|View full text |Cite
|
Sign up to set email alerts
|

The Mineral Oxide Contents of the Tegal Lenga Beach Iron Sand

Abstract: The research of determination of the oxide mineral contents of the Tegal Lenga Beach iron sand by using XRD has been done. Iron sand samples were taken from the top layer of the Tegal Lenga Beach sand. The three sand samples were taken from three different places which were separated at a distance of 15 m one another. The separation process is carried out using magnetic separation method. The characterization methods include mass fraction and X-ray diffraction (XRD). It obtained that the average mass fraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Magnetite particles are an interesting material to develop because of their potential in applications in various fields such as color pigments for industrial [8], biomedical material [9] [10] [11], heavy metal absorbing materials [6], anode materials for lithium batteries [12], etc. Based on the description above, a preliminary study has been carried out on the metal oxide content of the iron sand of Tegal Lenga Beach [13], and continued with the study of magnetite crystals extracted from the sand of Tegal Lenga Beach, which is reported in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetite particles are an interesting material to develop because of their potential in applications in various fields such as color pigments for industrial [8], biomedical material [9] [10] [11], heavy metal absorbing materials [6], anode materials for lithium batteries [12], etc. Based on the description above, a preliminary study has been carried out on the metal oxide content of the iron sand of Tegal Lenga Beach [13], and continued with the study of magnetite crystals extracted from the sand of Tegal Lenga Beach, which is reported in this paper.…”
Section: Introductionmentioning
confidence: 99%